Humour and Irony in Kourouma’s Novels - Ajayi, Samson Abiola (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
In a flavour of humour, Kourouma draws a trajectory of the lives of his heroes to portray the irony of life in each case. From Fama in Les soleils des indépendances to Birahima in Allah n’est pas obligé , including the King of Soba in Monnè, outrages et défis , as well as President Koyaga in En attendant le vote des bêtes sauvages, the life story of the protagonist in each case ended the opposite way to their initial expectations. This is in spite of all their efforts put in, both in the overt and in the covert, to achieve target. And in all the cases, the protagonists kept hoping for the best until their eventual ironic turn of events. This is the thrust of irony and humour in the four novels which this study has highlighted: the irony of the disillusionment being experienced by Africans as against the high hopes and expectations promised by the independence of the1960s. Keywords: Kourouma, humour, irony, satire, African literature,